To screen or not to screen medical students for carriage of multidrug-resistant pathogens? - Smelikova, E; Drevinek, P; Nyc, O; Brajerova, M; Tkadlec, J; Krutova, M (The Journal of hospital infection, 2023)
BACKGROUND: The carriage of multidrug-resistant (MDR) pathogens in medical students has not been studied extensively, despite the fact that they are in contact with patients and exposed to a hospital environment. AIM: To investigate the intestinal and nasal carriage of MDR pathogens among medical students and its association with their lifestyle and demographic data. METHODS: In 2021, first- and final-year medical students were invited to the study. Two rectal swabs were used for detection of extended-spectrum β-lactamase (ESBL)-producing, colistin-, tigecycline- or carbapenem-resistant Gram-negative bacteria and vancomycin-resistant enterococci. Nasal swab was used for Staphylococcus aureus culture. S. aureus isolates were characterized by spa typing; Gram-negative resistant isolates and meticillin-resistant S. aureus (MRSA) were subjected to whole-genome short and/or long sequencing. FINDINGS: From 178 students, 80 (44.9%) showed nasal carriage of S. aureus; two isolates were MRSA. In rectal swabs, seven ESBL-producing strains were detected. Sixteen students were colonized by colistin-resistant bacteria, three isolates carried the mcr-1 gene (1.7%). The mcr-9 (10.7%, 19/178) and mcr-10 (2.2%, 4/178) genes were detected by quantitative polymerase chain reaction, but only two colistin-susceptible mcr-10-positive isolates were cultured. The S. aureus nasal carriage was negatively associated with antibiotic and probiotic consumption. S. aureus and colistin-resistant bacteria were detected more frequently among students in contact with livestock. CONCLUSION: Medical students can be colonized by (multi)drug-resistant bacteria with no difference between first- and final-year students. The participation of students in self-screening increases their awareness of possible colonization by resistant strains and their potential transmission due to poor hand hygiene.
Keywords: studenti lékařství; Prevalence; Students, Medical; antibakteriální látky; kolistin; Surveillance; Whole-genome sequencing; Colistin; Humans; Chromosomally encoded; lidé; Methicillin-Resistant Staphylococcus aureus; Anti-Bacterial Agents; Staphylococcus aureus; Resistance; methicilin rezistentní Staphylococcus aureus; Bioinformatics